Rancang Bangun Aplikasi Toko Online Berbasis Website ATK Yudistira Jaya - Abyan, Muhammad Abdul Aziz; Surapati, Untung (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The rapid development of information technology has brought significant changes to the trading sector, including micro, small, and medium enterprises (MSMEs). This study aims to design and develop a website-based online store application for ATK Yudistira Jaya to enhance operational efficiency and expand market reach. The development method used in this system is the Waterfall model, with the Laravel framework for the backend and MySQL as the database. The test results indicate that the application meets the needs of both admins and customers, with key features such as a product catalog, ordering system, payment integration, and order management. The implementation of this application is expected to assist MSMEs in leveraging digital technology to improve their competitiveness.